Comparison of The Expository Approach and The Inquiry Approach in Improving Vocabulary Learning Outcomes Used by State Elementary School 10 South Rantau Labuhan Batu Regency - Maratimbo Harahap; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to compare the effect of the expository approach and the inquiry approach in improving vocabulary learning outcomes in sixth-grade students of SD Negeri 10 Rantau Selatan, Labuhan Batu Regency, in the 2025-2026 academic year. Vocabulary is an important material in teaching Indonesian which is the focus of this study. The expository approach involves the presentation of teaching materials that have been neatly prepared by the teacher, while the inquiry approach focuses on learning that demands active student involvement through the discovery process. The research method used is an experiment with an objective test instrument totaling 40 questions given after students have participated in learning using both approaches. This study aims to determine the differences in vocabulary learning outcomes of students taught using the expository approach and the inquiry approach. The results showed that the average value of vocabulary learning outcomes of students taught with the expository approach was 72.57, which can be categorized as good. Meanwhile, the learning outcomes of students taught with the inquiry approach obtained an average value of 85.07, which can be categorized as very good. Based on data analysis and statistical tests, there was a significant difference between the two approaches, where the inquiry approach showed a better increase in vocabulary learning outcomes by 17.22% compared to the expository approach. Thus, it can be concluded that the use of the inquiry approach is more effective in improving vocabulary learning outcomes of grade VI students of SD Negeri 10 Rantau Selatan, Labuhan Batu Regency in the 2025-2026 academic year